"Adicción de carbonato de calcio en la dieta para mejorar parámetros productivos en ponedoras ISA BROWN Fase I" - Vera Rodríguez, José Humberto (2012)
SUMMARY The addition of calcium carbonate was evaluated in the last hours of the afternoon in the diet of egg-laying Isa Brown to optimize the index zootechnical and to improve the quality of the shell, being used 200 hens in production phase I. Three levels of calcium carbonate were used (0,50; 1,00; 1,50 g/hens/day) plus a witness treatment to which was not added calcium carbonate. It was used 10 repetitions by treatment, the experimentation lasted 12 weeks. The statistical evaluation was carried out with a Totally Random Design Blocks with its analysis of simple variance, finding averages that were adjusted with the Tukey Test. No statistical significant difference (p<0,05) was found in the parameters: hens weight; food consumption; posture percentage; weight of the egg; accumulated egg; mass egg and nutritious conversion, but it was a high statistical significance in the shell thickness obtaining a better average when adding 1,50 g/hens/day, and when carrying out the regression analysis with the weight of the egg a coefficient of correlation of 0,69 it was reached guaranteeing this difference. It can be concluded that the addition of 1,50 g/hens/day of calcium carbonate improves the shell thickness significantly reducing the number of broken eggs and as for the economic analysis it was demonstrated that marginal return rate presented it the treatment with 1,50 g/hens/day with 10,76% when adding this dose in the last hours of the afternoon, with a granulometry of 2 to 4 mm.